2005
DOI: 10.3171/jns.2005.102.3.0434
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife surgery for trigeminal neuralgia: outcomes and prognostic factors

Abstract: At the last follow up, GKS effected pain relief in 44% of patients. Some degree of pain improvement at 3 years post-GKS was noted in 70% of patients with TN. Although less effective than MVD, GKS remains a reasonable treatment option for those unwilling or unable to undergo more invasive surgical approaches and offers a low risk of side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
2
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(124 citation statements)
references
References 36 publications
8
111
2
3
Order By: Relevance
“…However, other clinical investigators have reported lower incidence rates of posttreatment facial numbness. 10,15,17,23,29 The development of numbness was slightly higher in the group of patients with previous surgery in our study. However, this difference was not statistically significant.…”
Section: Neurosurg Focus / Volume 23 / December 2007mentioning
confidence: 58%
See 3 more Smart Citations
“…However, other clinical investigators have reported lower incidence rates of posttreatment facial numbness. 10,15,17,23,29 The development of numbness was slightly higher in the group of patients with previous surgery in our study. However, this difference was not statistically significant.…”
Section: Neurosurg Focus / Volume 23 / December 2007mentioning
confidence: 58%
“…[4][5][6][12][13][14][15][30][31][32] The effect of the latency period after SRS in our study is comparable with the findings in previously reported series. 8,17,22,23,29,31 Interestingly, patients with previous surgery seem to be more frequently late responders to GKS than patients with no history of previous surgery. Our excellent and good outcome rates are comparable to those reported in previously published studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By administering 60-90 Gy with a Co-60 source through a 4 mm aperture, the Gamma Knife has been shown to produce conformal isodose distributions and correspondingly excellent clinical results [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%